A conceptual model for driving green purchase among Indian consumers - Prashant Trivedi (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2015)
Marketing is considered as responsible for increasing consumerism and overuse of limited resources. An endeavour to promote sustainable consumption is the need of the hour and an answer to growing concerns towards it is required. Marketing can be used as a tool to promote sustainability and increase responsible consumption. Many products which have energy saving potential can be successfully promoted through marketing activities. Increasingly, consumers are becoming aware about the issue and through constant marketing efforts green products and sustainable consumption can be taken to a high level. Contextual factors like value for money, features and selling point communication can play a crucial role in increasing the purchase of green products. Several studies are being conducted in this area but there is still a need for more research particularly in India. This paper will be a contribution to the existing area of knowledge and will focus on discovering the role which marketing can play in promoting sustainability among consumers in India. The factors which are responsible for sustainable consumption are explored and a conceptual model has been suggested which may help marketers in promoting green products and provide a platform for further research.
Keywords: M00; M30; M31; Q50; 650; green purchase behaviour; sustainability; selling point; contextual factors